The big four : the curious past and perilous future of the global accounting monopoly - Gow, Ian D.; Kells, Stuart (Berrett-Koehler Publishers, Inc., 2018)
"With staffs that are collectively larger than the Russian army, the Big Four accounting firms are a keystone in global finance --but do they really provide stability and safety? Leading scholar Ian Gow and award-winning writer (and former KPMG director) Stuart Kells warn that a house of cards may be about to fall. Across the globe, the so-called Big Four accounting and audit firms - Deloitte, PricewaterhouseCoopers, Ernst & Young, and KPMG - are massively influential. Together, they earn more than $100 billion annually and employ almost one million people. In many profound ways, they have changed how we work, how we manage, how we invest and how we are governed. Stretching back centuries, their history is a fascinating story of wealth, power and luck. But today, the Big Four face an uncertain future - thanks to their push into China; their vulnerability to digital disruption and competition; and the hazards of providing traditional services in a new era of transparency. Surprisingly colorful and unquestionably authoritative, this account of the past, present and likely future of the Big Four is essential reading for anyone perplexed or fascinated by professional services, working in the industry, contemplating joining a professional services firm, or simply curious about the fate of the global economy"--